2015
DOI: 10.5942/jawwa.2015.107.0121
|View full text |Cite
|
Sign up to set email alerts
|

Full‐Scale Ozone–Biofiltration: Seasonally Related Effects on NOM Removal

Abstract: Performance of full‐scale ozone–biofiltration was investigated over 14 months to determine the potential effects of seasonally related changes in water temperature and quality on the removal of natural organic matter fractions. The biofilters removed on average 12% of dissolved organic carbon, 31% of biopolymers, 6% of humic substances, 10% of humic building blocks, 31% of low‐molecular‐weight (LMW) acids/LMW humics, 14% of LMW neutrals, and 52% of assimilable organic carbon. The biofilters exhibited an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 43 publications
(56 reference statements)
4
19
0
Order By: Relevance
“…These concentrations fell outside the typical range of ATP concentrations (i.e., 100–1,000 ng ATP/cm 3 media) identified for drinking water biofilters (Pharand et al 2014). In that work, Pharand et al (2015) sampled biomass during an individual filter cycle as opposed to concentrated sampling at the start of a filter cycle. The current study highlighted that determining ATP concentration at the start of a filter cycle and within a filter cycle was important for understanding the range of expected ATP concentrations in biofiltration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These concentrations fell outside the typical range of ATP concentrations (i.e., 100–1,000 ng ATP/cm 3 media) identified for drinking water biofilters (Pharand et al 2014). In that work, Pharand et al (2015) sampled biomass during an individual filter cycle as opposed to concentrated sampling at the start of a filter cycle. The current study highlighted that determining ATP concentration at the start of a filter cycle and within a filter cycle was important for understanding the range of expected ATP concentrations in biofiltration.…”
Section: Resultsmentioning
confidence: 99%
“…In GAC filters undergoing conversion to biologically activated carbon biofiltration, biofilters reached steady state with respect to DOC removal at the same time that biomass steady state, as measured by ATP, was reached (Velten et al 2011). In contrast, other analyses have shown that biomass concentration in the top media layer in drinking water biofilters, as measured by phospholipids, ATP, and/or fluorescein diacetate (FDA) hydrolysis, is not directly related to biodegradable organic matter (BOM) (Emelko et al 2006) or DOC removal (Pharand et al 2015, 2014; Stoddart & Gagnon 2015) in pilot‐ or full‐scale biofilters.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Rapid rate gravity biofiltration has been practiced in major Western European waterworks since the 1970s (Heilker 1979, Sontheimer et al 1978). During the last decade, biological filtration has been gaining popularity in drinking water treatment in the United States and Canada, and its benefits are being recognized (Hallé et al 2015, Pharand et al 2015, Schulz 2014). Biofiltration is aerobic, rapid rate filtration through traditional granular media (e.g., granular activated carbon [GAC], anthracite, sand) that have developed a biofilm capable of degrading organic matter.…”
Section: Defining Biological Filtrationmentioning
confidence: 99%
“…Several studies have concluded that nutrient supplementation could be beneficial in optimizing the performance of biofilters (Granger, Stoddart, & Gagnon, ; Lauderdale et al, ), whereas others have found no significant benefit (Azzeh, Taylor‐Edmonds, & Andrews, ; McKie et al, ; Pharand, Van Dyke, Anderson, Yohannes, & Huck, ). These contradictory results emphasize that more information is needed to better understand the potential benefits of nutrient augmentation.…”
Section: Introductionmentioning
confidence: 99%